EDUCATIONAL PROGRAMMING ON RADIO BELGRADE DURING THE SECOND WORLD WAR - PAULINA ČOVIĆ (Истраживања, 2024)
Drawing from archival documents, periodicals, and relevant literature, this paper analyzes the role and significance of educational programming broadcast by the Radio Belgrade within the broader propaganda efforts of Milan Nedić’s government. The paper begins with a theoretical explanation of how media functions in education. This will be followed by the use of radio as an instructional tool in Serbian schools during the first half of the twentieth century. The analysis includes talks given during what was called Prosvetni čas (Educational Hour), a radio program broadcast in early 1944. Research has shown that, in a time of strong ideological influence on the educational process, the state educational authorities encouraged the use of any available means to achieve their political and propaganda-based ideological goals. Radio shows were produced for students during the 1930s and during the Second World War according to a similar model that made use of different content.